Doing Diversity in Higher Education : Faculty Leaders Share Challenges and Strategies - Brown-Glaude, Winnifred R., 1966- (Book collections on Project MUSE., 2009)
Using case studies from universities throughout the nation, Doing Diversity in Higher Education examines the role faculty play in improving diversity on their campuses. The power of professors to enhance diversity has long been underestimated, their initiatives often hidden from view. Winnifred Brown-Glaude and her contributors uncover major themes and offer faculty and administrators a blueprint for conquering issues facing campuses across the country. Topics include how to dismantle hostile microclimates, sustain and enhance accomplishments, deal with incomplete institutionalization, and col.